Dari Somba Opu Ke Makassar Evolusi Pelabuhan dan Peran Pinisi dalam Jaringan Perdagangan Maritim (Abad ke 19-20) - Tamara Siti Hikmah; Syaripatu Dai'mah; Nafatul Aimah; Abd Rahman Hamid; Agus Mahfuddin Setiawan (Universitas Negeri Gorontalo, 2026)
This study examines the transformation of Somba Opu Port into Makassar Port and the role of Pinisi vessels in maritime trade networks from the nineteenth to the early twentieth century. It aims to analyze the development of Makassar Port as a colonial trading center in eastern Netherlands Indies. Employing the historical method with a maritime history approach through heuristic research, source criticism, interpretation, and historiography the study finds that Somba Opu Port served as the initial foundation of Makassar’s commercial harbor, which later shifted to the Ujung Pandang Fortress (Fort Rotterdam) area following Dutch colonial consolidation. During the colonial period, Makassar Port emerged as a major trading hub in eastern Indonesia, marked by the rise of steamship traffic and the dominance of the Koninklijke Paketvaart Maatschappij (KPM). Meanwhile, Pinisi vessels continued to play a significant role in inter-island trade by transporting commodities such as copra, trepang, rice, and forest products. In conclusion, the development of Makassar Port reflects an interaction between colonial maritime modernization and the persistence of local maritime traditions, while the endurance of Pinisi ship technology demonstrates the adaptability of maritime communities to economic change and global trade systems.